Aneka Olahan Pangan Talas Beneng (Xanthosoma undipes K. Koch) Sebagai Pangan Sehat Bebas Gluten dan Kasein - Sayidatul Maslahah; Zidan Ramzy; Yunita Dwi Pebri Arini; Sulastri Juliyah; Talitha Fawnia; Mita Yuni Saputri; Sekar Ayu Septia Ningrum (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2025)
This community service activity focuses on the utilization of Talas Beneng (Xanthosoma undipes K. Koch), a tuberous plant native to Banten Province, as a healthy alternative food source free from gluten and casein. The program was implemented through the Holistic School Field Introduction (PLP) by students from Sultan Ageng Tirtayasa University at State Special School 02 Serang City. The method employed was qualitative, with a direct practice approach through training in preparing various processed products based on talas beneng, such as steamed cakes, brownies, cookies, and sticks. The activity involved three intellectually disabled students from junior and senior high school levels, along with PLP students and a culinary arts teacher. The primary objectives of the program were to enhance life skills, independence, and awareness of the importance of diversifying healthy local food sources. The results indicate an improvement in participants' abilities to recognize local food ingredients, process them into nutritionally valuable products, and strengthen collaboration between universities and schools in inclusive education. This program demonstrates that the utilization of local food resources can serve as an effective strategy to support food security, social empowerment, and holistic education.